The artistic significance of the implicit metaphor in the poem “On the Covenant of Arabism We Shall Remain” by Mufdi Zakaria - allem, hichem; belairdouh, thoulaitha (El Omda in Linguistics and Discourse Analysis, 2025)
Metaphor is one of the linguistic techniques widely employed by poets throughout history in their poetic production. To examine one aspect of this phenomenon, we conducted a study entitled: The Artistic Significance of the Implicit Metaphor in the Poem “On the Covenant of Arabism We Shall Remain” by the Algerian revolutionary poet Mufdi Zakaria. This study aims to reshape the reader’s perception and immerse them in the lexical meanings and linguistic connotations repeatedly employed in the text, thereby highlighting the strengths, aesthetic values, and linguistic deviations in his poetic style. We adopted the descriptive approach as a guiding method to uncover the internal layers of meaning within the implicit metaphors used by the poet. These metaphors rely on personification and embodiment, transforming abstract meanings from their internal, emotional depths into tangible, concrete forms, while attributing to them expressive and profound qualities. The metaphorical implications identified in this study invite us to pay tribute to this remarkable poet, who, through his poem, succeeded in reflecting the level of the Algerian people and expressing their ultimate goal of achieving freedom. Modernism and symbolism also played a significant role across its verses.